Primary diffuse large B-cell lymphoma of the breast with rare growth pattern mimics lobular carcinoma: a case report - Su, Si; Sun, Jian; Pan, Boju; Jia, Congwei (Frontiers in Oncology, 2025)
We report a case of a 34-year-old female presenting with a rapidly enlarging right breast mass. Ultrasonographic evaluation revealed a large solid mass accompanied by ipsilateral axillary lymphadenopathy. Histopathological examination of the biopsy specimen showed an unusual rowth pattern of atypical cells, characterized by perivascular “target-like” and “soldier-like” arrangements, which closely mimicked lobular carcinoma and posed significant challenges to the diagnostic process. Immunohistochemical (IHC) staining was crucial in differentiating this lymphoma from breast carcinoma, with positive results for LCA, CD20 and CD19, and negative for ER and PR. Following multiple rounds of IHC testing, the final diagnosis was confirmed as diffuse large B-cell lymphoma (DLBCL), non-special type (NOS). Further staging revealed no distant metastasis. The case of primary breast DLBCL highlights us a rare perivascular target-like growth pattern of tumor cells. The inclusion of LCA in the IHC panel is recommended to aid in accurate diagnosis and guide appropriate treatment, especially when histological patterns are ambiguous.